Draft Annual Plan 2001-02 Scheme-wise Details - Planning Commission (Planning Commission, 2001)
The Union Territory of Pondicherry consists of four regions, namely Pondicherry, Karaikal, Mahe and Yanam lying geographical isolated from one another. Pondicherry region which is on the east coast, about 162 Kms. South of Chennai is the largest of all the four and consists of 12 scattered areas lying between 1140' N & 79 52' E. Karaikal region is about 150 Kms. South of Pondicherry and is surrounded by Nagai district of Tamil Nadu. It is located between 10 49' and 11 01'N & 79 43' and 79 52'E. Yanam region is located between 16 42' and 16 46' N and 82 11' and 82 19' E at about 840 Kms. North East of Pondicherry near Kakinada in Andhra Pradesh. Mahe region lies almost parallel to Pondicherry between 11 42' and 11 43' N and 75 31' and 75 32' E at 653 Kms. away on the West Coast near Tellicherry in Kerala.